Models of everywhere revisited: A technological perspective. (December 2019) - Blair, Gordon S.; Beven, Keith; Lamb, Rob; Bassett, Richard; Cauwenberghs, Kris; Hankin, Barry; Dean, Graham; Hunter, Neil; Edwards, Liz; Nundloll, Vatsala; Samreen, Faiza; Simm, Will; et al.
Abstract : The concept 'models of everywhere' was first introduced in the mid 2000s as a means of reasoning about the environmental science of a place, changing the nature of the underlying modelling process, from one in which general model structures are used to one in which modelling becomes a learning process about specific places, in particular capturing the idiosyncrasies of that place. At one level, this is a straightforward concept, but at another it is a rich multi-dimensional conceptual framework involving the following key dimensions: models of everywhere, models of everything and models at all times, being constantly re-evaluated against the most current evidence. This is a compelling approach with the potential to deal with epistemic uncertainties and non-linearities. However, the approach has, as yet, not been fully utilised or explored. This paper examines the concept of models of everywhere in the light of recent advances in technology. The paper argues that, when first proposed, technology was a limiting factor but now, with advances in areas such as Internet of Things, cloud computing and data analytics, many of the barriers have been alleviated. Consequently, it is timely to look again at the concept of models of everywhere in practical conditions as part of a trans-disciplinary effort to tackle the remaining research questions. The paper concludes by identifying the key elements of a research agenda that should underpin such experimentation and deployment. Highlights: Models of everywhere is historically an important concept in environmental modelling. The approach is fundamentally about modelling of place as a learning process. Deployment has been restricted due to underlying technological limitations. It is timely to revisit this concept as these limitations are being overcome. A trans-disciplinary effort is required to resolve remaining research questions.